Research Progress on Dioxin Prevention and Control Technologies in the Entire Process of Domestic Waste Incineration - Yongyi MA; Qianqian LI; Bohua SUN; Jing MENG; Bin SHI; Yangzhao SUN; Guijin SU (能源环境保护)
The prevention and control of dioxin formation during domestic waste incineration plays a crucial role in the harmless disposal of solid waste. This paper systematically summarizes three mechanisms of dioxin formation during the entire incineration process under high-temperature and low-temperature conditions: high-temperature homogeneous synthesis, precursor synthesis, and de novo synthesis, identifying chlorine sources, carbon sources, metals, oxygen, and temperature as key influencing factors. This study focuses on three main stages of domestic waste management, including collection, incineration, and waste disposal, and elaborates on various dioxin reduction technologies applicable to each stage, including waste source blending and conditioning, pollution control during incineration, and end-of-pipe treatment of flue gas and fly ash. The fundamental principles and simple operational methods of each technology are elucidated, and strategies for dioxin prevention throughout the entire domestic waste incineration process are proposed. By screening incoming waste and co-combustion with selected industrial solid waste, the contents of chlorine sources and metals can be reduced, while improving the calorific value, thus reducing dioxin formation at the source. Products of incomplete combustion from domestic waste can generate dioxins through precursor synthesis. Optimizing "3T+E" (Temperature, Time, Turbulence, and Excess-Air) combustion conditions can minimize the generation of products of incomplete combustion, thereby preventing dioxin formation during incineration. The use of inhibitors can control dioxin formation through three mechanisms: passivating reactive metals, consuming chlorine sources, and inhibiting precursor synthesis. Currently, common types of inhibitors include sulfur- and nitrogen-based inhibitors, phosphorus-based inhibitors, and alkaline inhibitors. Dioxins generated during incineration primarily exist in flue gas and fly ash. Various technologies have been developed to adsorb and degrade dioxins in flue gas, preventing them from entering the atmosphere and posing threats to the ecological environment and human health. Activated carbon technology has proven effective in adsorbing dioxins from flue gas. Catalytic degradation technology is an important method for treating dioxins in flue gas, as it not only destroys dioxin structures but also enables the synergistic removal of other pollutants, for example, selective catalytic reduction (SCR) technology can simultaneously remove dioxins and NOx. Commonly used dioxin catalysts can be classified into transition metal oxide catalysts and noble metal catalysts. Some dioxins accumulate in fly ash, and thermal treatment technologies such as co-processing in cement kilns, microwave heating, and hydrothermal treatment can effectively decompose dioxins at high temperatures, achieving efficient removal of dioxins from fly ash. This paper provides a systematic comparison and summary of the advantages, disadvantages, and technological maturity of the aforementioned dioxin prevention and control technologies across different processes. Furthermore, current research challenges and future research directions are proposed, providing a reference for the development and industrial application of dioxin control technologies in the incineration process.